System analysis of factors in the pathogenesis of drusen formation in AMD (Ukrainian Journal of Ophthalmology, 2025)
Background: Age-related macular degeneration (AMD) is a major cause of visual loss in elderly individuals. However, the involvement of cell receptors in the initiation of retinal disorder in AMD has not been duly reflected in the literature. The absence of system analysis of pathogenetic mechanisms of drusen formation restricts the possibilities for researchers to develop methods of treatment and prevention of early AMD.Purpose: To carry out system analysis of novel factors in the pathogenesis of drusen formation in AMD.Material and Methods: This prospective study included 109 patients (186 eyes) with intermediate stage of dry AMD. All patients received a detailed eye examination before and in the course of treatment. We used receptor ligands (specifically, adenosine triphosphate (ATP), adenosine diphosphate (ADP), adenosine, platelet activation factor (PAF), adrenaline and isadrine) to examine the functional activity of platelet receptors. Platelet aggregation was assessed by the turbidimetric method. The effect of platelet reactivity on the formation of drusen in the RPE was also assessed.Results: The comparison of Group 1 patients with and without drusen (subgroups A and B, respectively) versus controls with regard to platelet reactivity indicated that hyperreactivity of alpha-2 adrenoreceptors reflected early accumulation of metabolite residues in RPE cells and appearance of drusen in the retina. An increase in drusen numbers in the RPE in Group 2 (subgroup C) patients with early dry AMD compared to subgroup B with was reflected by increased activity of P2X purine receptors (р < 0.05) and A2A adenosine receptors (р < 0.001). In group 3 (subgroup E) patients with intermediate stage of dry AMD, an increase in the size of drusen was accompanied by changes in activity of the four examined platelet receptors, with increases in sensitivity of alpha-2 adrenoreceptor, P2X and PAF receptors, and a decrease in sensitivity of beta-2 adrenoreceptor.Conclusion: Platelet receptors reactivity reflected the effect of factors in the pathogenesis of AMD on drusen formation, and, therefore, can be used for prediction of the risk of disease progression.
Keywords: age-related macular degeneration; platelet receptors; retinal pigment epithelium; drusen formation